Feedback: understanding strategies and impact on EFL learning and teaching contexts - Espinosa Torres, David Felipe; González Bejarano, Iván Camilo; Moreno Restrepo, Juliana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Feedback is a powerful tool that has a significant influence on student success. Its meaningful impact on learning and teaching processes has been well-documented. However, there is minimal research concerning the impact of feedback strategies on foreign language learning. This article seeks to provide a theoretical and practical understanding of the impact of feedback on foreign language teaching and learning processes. This is done through a case study research conducted in a private institution in Bogotá, Colombia. The evidence demonstrates that the feedback strategies used and the manner in which they are administered influence their effectiveness. Three main strategies were observed and analyzed: corrective, motivational, and developmental. This article concludes with a suggestion to make feedback an explicit policy of teachers’ education programs in the country.